1991
DOI: 10.3354/dao011009
|View full text |Cite
|
Sign up to set email alerts
|

Postvalvular enterocytes in feral and farm-reared sea bass Dicentrarchus labrax; hypervacuolization related to artificial feed

Abstract: ABSTRACT. The postvalvular intestine of sea bass, which is involved in the absorption of protein macromolecules by pinocytosis, was studied by light microscopy, scanning electron microscopy and transn~ission electron microscopy. We describe the morphofunctional characteristics of this enteric region for control specimens from a natural environment. In comparison, we distinguished a disease affecting the intestine of farm-reared sea bass nourished with artificial feed. The disease is characterized by vacuolizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Most individuals of the F+ population have enlarged ovoid supra-nuclear vacuoles, some filled with dense material. Similar enlarged vacuoles have already been observed in farm-reared sea bass overfed with artificial feed (Deplano et al, 1991). It is thus hypothesized that the F+ group is not as efficient in feed assimilation as the F-group.…”
Section: Accepted Manuscript Discussionsupporting
confidence: 70%
“…Most individuals of the F+ population have enlarged ovoid supra-nuclear vacuoles, some filled with dense material. Similar enlarged vacuoles have already been observed in farm-reared sea bass overfed with artificial feed (Deplano et al, 1991). It is thus hypothesized that the F+ group is not as efficient in feed assimilation as the F-group.…”
Section: Accepted Manuscript Discussionsupporting
confidence: 70%
“…Moreover, Deplano et al [13] and Sklan et al [14] stated that the abilities to absorb protein in the intestine of carnivorous fish are welldeveloped, but carbohydrate absorption is low compared to omnivorous and herbivorous fishes, while the absorption of protein is less developed in herbivorous fish. However the activity of pancreatic enzymes was maximal in anterior intestine and decreased distally.…”
Section: Discussionmentioning
confidence: 99%
“…Although, Iida and Yamamoto [16] and Deplano et al [13] reported the presence of pinocytotic vesicles and numerous vacuoles in the posterior intestine of both herbivorous and carnivorous fishes, which considered evidence of the uptake of undigested protein-like substances. This process begins by the proteins, which are incorporated into pinocytotic vesicles and transported to supranuclear vacuoles where they accumulate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was already reported in farm-reared Dicentrarchus labrax fed with commercial pellets and compared to fish from fishing fed with natural prey with 70-80% water content. Pronounced hypertrophy of the intestinal folds and abrasion-induced degeneration of the epithelium has been demonstrated in aquaculture fish (Deplano et al 1991).…”
Section: Resistance To Bacterial Infectionmentioning
confidence: 99%